Kebangkitan Nasional: Merawat Nasionalisme Kaum Muda Indonesia - Rizqon Halal Syah Aji (ADALAH, 2020)
AbstractThe spirit of regrowing the nationalism of Indonesian youth aims to answer the challenges and obstacles caused by the Pandemic Covid-19 outbreak. Indonesian young people who are classified as productive labor age are the key to the sustainability of Indonesia's economic growth which should not collapse due to the impact of the Pandemic Covid-19 outbreak. This group of workers is called the millineal generation. The young group lives in an atmosphere of technology utilization and digitalization. Maximizing technology and digitalization will sustain millennial groups in giving birth to demographic bonuses. Millennial groups should not ignore the windows of opportunity in welcoming demographic bonuses. There are many challenges for millennial youth groups, in addition to being able to utilize technology to maximize productive work efforts, but the habit of using digital technology must not change the character of the Indonesian people who are always in a relationship between individuals and mutual cooperation, tolerance and upholding cultural values that promote humanity. The character of the nation is a form of Indonesian nationalism.Keywords; Nationalism, Young Indonesians, Milineal, Pandemic Covid-19, Demographic Bonus.AbstraksSemangat menumbuhkan kembali nasionalisme kaum muda Indonesia bertujuan untuk menjawab tantangan dan hambatan karena wabah Pandemi Covid-19. Kaum muda Indonesia yang tergolong usia tenaga kerja produktif merupakan kunci keberlangsungan pertumbuhan ekonomi Indonesia yang tidak boleh runtuh karena dampak wabah Pandemi Covid-19. Kelompok tenaga kerja tersebut dinamakan sebagai generasi milineal. Kelompok muda hidup dalam suasana pemanfaatan teknologi dan digitalisasi. Memaksimalkan teknologi dan digitalisasi akan menopang kelompok milenial dalam melahirkan bonus demografi. Kelompok milenial tidak boleh mengabaikan windows of oportunity dalam menyambut bonus demografi. Banyak tantangan kelompok muda milenial, selain harus mampu memanfaatkan teknologi untuk memaksimalkan upaya kerja yang produktif, akan tetapi habit penggunaan teknologi digital tidak boleh mengubah karakter bangsa Indonesia yang senantiasa melakukan relasi antara individu dengan gotong royong, tenggang rasa serta menjunjung nilai budaya yang mengedepankan kemanusiaan. Karakter bangsa tersebutlah yang merupakan corak nasionalisme Indonesia.Kata Kunci; nasionalisme, kaum muda Indonesia, milineal, Pandemi Covid-19, bonus demografi.